The effectiveness of a program that is based on (STEM) preface in developing of teaching performance skills for student teachers in Faculty of Education - Sana’a - Sharf Al-Deen, Eman Yahya Ahmed Hamod (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the effectiveness of program that is based on (STEM) preface in development of teaching performance skills for student teachers in Faculty of Education - Sana’a and to achieve the aim of this study. The study used the descriptive and semi-experimental curriculums, and a training program is designed according to(STEM) preface and an observation rating scale of teaching performance skills. The sample of study consisted of (22) students of Physics departments, level4 in the academic year (2022-2023). It represented one trained group. The result of the study resulted some differences that have statistical significances between grade averages of marks at student teachers in the two applications: pre and post for the observation rating skill of teaching performance skills which is good for the post application. And there are no differences, that have statistical significance between grade average of marks at student teachers in the applications: post and sequential of the observation rating scale at teaching performance skills. In light of the results the study recommended several recommendations, the most important of which are the inclusion of the (STEM) preface in the university studying curriculums throughout definitional and performed activities, training courses and workshops for teachers in teaching according to (STEM).